(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The educational environment of an educational institution is part of a person’s living environment. Educational institutions, as a social institution of society, are subjects of security, and the importance of studying the psychological safety of an individual in an educational environment lies in the fact that an educational institution (school, vocational school, technical school, university), including the younger generation, adults and family, is able to build their local (private) security system both through training and education, and through solving development problems. The purpose of the article is to study the psychological, pedagogical and methodological literature on the problem of psychological safety in the educational environment. Also, process and interpret the research results.